2010
DOI: 10.1177/0032329210381240
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening Labor Standards Enforcement through Partnerships with Workers’ Organizations

Abstract: Structures of employment in low-wage industries, a diminished wage and hour inspectorate, and an unworkable immigration regime have combined to create an environment where violations of basic workplace laws are everyday occurrences. This article identifies four “logics” of detection and enforcement, arguing that there is a mismatch between the enforcement strategies of most federal and state labor inspectorates and the industries in which noncompliance continues to be a problem. In response, the authors propos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
85
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(87 citation statements)
references
References 17 publications
1
85
0
1
Order By: Relevance
“…These agencies and centers often have extensive contacts among these worker groups and regularly receive reports of statutory violations. Fine and Gordon (2010) and Fine (2014) suggest that funding and empowering such groups to undertake inspections would significantly increase the number of workplace inspections and improve the targeting of so-called bad-actor employers. The discovery of violations by a civil society group (or an employer refusal to cooperate with such a group) would then trigger a complaint to government inspectors.…”
Section: Discussionmentioning
confidence: 99%
“…These agencies and centers often have extensive contacts among these worker groups and regularly receive reports of statutory violations. Fine and Gordon (2010) and Fine (2014) suggest that funding and empowering such groups to undertake inspections would significantly increase the number of workplace inspections and improve the targeting of so-called bad-actor employers. The discovery of violations by a civil society group (or an employer refusal to cooperate with such a group) would then trigger a complaint to government inspectors.…”
Section: Discussionmentioning
confidence: 99%
“…Passant de seulement cinq en 1992 à 170 en 2009 (Fine et Gordon, 2009), ces « quasi-syndicats » (Heckscher et Carré, 2006) prennent des formes diverses et s'adressent à un large éventail de travailleurs précaires, des salariés de la restauration rapide aux conducteurs de taxis formellement indépendants en passant par les laveurs de voitures. Ils sont parfois ouverts à tous les travailleurs d'une zone géographique mais souvent marqués par une communauté ethnique donnée (ce qui revient au même dans les zones urbaines ségréguées).…”
Section: Résumé De L'articleunclassified
“…Moreover, few studies address migrant agency from a comparative perspective. Studies have shown that community initiatives, migrant organisations and worker centres have been successful in linking up with migrant interests and play a role in enhancing opportunities for agency and change (Fine 2007;Fine and Gordon 2010). The impact of these societal actors may be explored more through comparative studies.…”
Section: Future Researchmentioning
confidence: 99%